Detection of RET (rearranged during transfection) variants and their downstream signal molecules in RET rearranged lung adenocarcinoma patients. (March 2018) - Kim, Jeong- Oh; Shin, Jung -Young; Kim, Min Young; Son, Kyoung Hwa; Jung, Chan Kwon; Kim, Tae-Jung; Kim, Su Young; Park, Jae Kil; Sung, Sook Whan; Bae, Sang Ju; Min, Hyun Jung; Kang, Jin- Hyoung
Abstract: Background: We screened resected tumor tissues from patients with lung cancer for EGFR mutations, ALK rearrangements, and rearranged during transfection ( RET ) gene variants (including RET rearrangements and the Kinesin Family Member 5B (KIF5B ) -RET fusion gene) using various methods including reverse transcription polymerase chain reaction (RT-PCR), transcript assays, fluorescence in situ hybridization (FISH), and immunohistochemistry (IHC). We also examined the protein expression of associated downstream signaling molecules to assess the effect of these variants on patient outcome. Method: We constructed a tissue microarray (TMA) comprising 581 resected tumor tissues from patients with lung adenocarcinoma and analyzed the microarray by both FISH (using RET break-apart and KIF5B-RET SY translocation probes) and a commercial RET transcript assay. We evaluated the expression of RET and RET-related signaling molecules, including p-AKT and p-ERK, by TMA -based IHC staining. Results: Among the 581 specimens, 51 (8.8%) specimens harbored RET rearrangements, including 12 cases (2.1%) carrying a KIF5B-RET fusion gene. Surprisingly, RET expression was lower in KIF5B-RET fusion gene-positive than in RET wild-type specimens. We detected activating EGFR mutations in 11 (21.6%) of the 51 RET variant-positive specimens. Among the KIF5B-RET fusion gene-positive specimens, p-ERK expression was significantly lower in the EGFR mutation subgroup showing RET expression than in the EGFR mutation subgroup that did not express RET. Similarly, the RET rearrangement group showed significant variation in the expression level of p-AKT (P = 0.028) and p-ERK, whose expression remarkably increased in specimens not expressing RET. The expression of p-ERK markedly increased in the RET rearrangement group regardless of RET expression. Conclusion: This result suggests that a combination of RET and ERK inhibitors may be an effective treatment strategy for lung adenocarcinoma patients harboring RET variants. Highlights: FISH is clinically applicable as well as RT-PCR for RET variants analysis. We detected the EGFR mutation and KIF5B-RET fusion gene in lung cancer. Expression of RET- associated signaling molecules varied in RET variant-positive groups. The KIF5B-RET fusion gene increased and inhibited p-ERK expression. RET and ERK inhibitors may be combined to treat lung adenocarcinoma with RET variants.